Case Report: Unraveling a web of clots: marantic endocarditis as a paraneoplastic manifestation of lung cancer - Forier, Bart; Staels, Frederik; Bivort, Dorian; Ralki, Mike (Frontiers in Oncology, 2026)
Marantic or non-bacterial thrombotic endocarditis (NBTE) is an uncommon but clinically important complication of malignancy, driven by a profound hypercoagulable state. It occurs most frequently in advanced adenocarcinomas and can present with a wide spectrum of thrombotic events, often mimicking infective endocarditis or other embolic disorders. We describe a rare presentation of metastatic EGFR-mutated lung adenocarcinoma complicated by NBTE, pulmonary embolism, splenic infarction, and acute coronary artery thrombosis. The diagnosis was supported by negative blood cultures, evidence of systemic emboli, and echocardiographic detection of a tricuspid valve vegetation. Management included prompt anticoagulation and initiation of targeted EGFR-directed therapy, which resulted in significant clinical and radiologic improvement, including complete resolution of the valvular lesion. This case underscores the need for heightened clinical suspicion for NBTE in patients with malignancy or unexplained embolic events, particularly when sterile valvular vegetations are identified. It also highlights the central role of effective cancer treatment—alongside anticoagulation—in reversing the prothrombotic state that drives NBTE.